The Caucasus Crisis: International Perceptions and Policy Implications for Germany and Europe - Hans-Henning Schröder (Stiftung Wissenschaft und Politik (SWP), 2008)
During the second week of August 2008 a local conflict in South Ossetia suddenly flared up into a conflagration on an international scale. Russia's decision to answer the Georgian attack on South Ossetia with a massive military intervention and to "punish" Georgia's wayward leadership triggered an international crisis. The brief analyses collected here examine how the Caucasus crisis has been perceived in the most important affected states and international organizations and outline the options that ensue. Alongside the question of how the crisis itself was managed, three themes are uppermost: a peaceful European order extending beyond the borders of the European Union, stronger political integration within the EU, and defining the role of NATO in an expanded Europe.
Keywords: 320